The Relationship Between Metabolic Syndrome and Depression: A Literature Review - Fitri Rahmariani (Scientia Psychiatrica, 2022)
Depressive disorders are a group of disorders with characteristics of loss of happiness, feeling useless or desperate, withdrawn or uninterested in common activity, and loss of energy or hypoactivity almost every day. Metabolic syndrome (MetS) is a clustering of conditions consist of central obesity, dyslipidemia, glucose intolerance, and hypertension. Both diseases are considered important risk factors of morbidity and cause of quality of life impairment. Some mechanisms are submitted to explain the correlated mechanism between MetS and depression.